Research Anthology on Computational Thinking, Programming, and Robotics in the Classroom 2022
DOI: 10.4018/978-1-6684-2411-7.ch026
|View full text |Cite
|
Sign up to set email alerts
|

Using Dr. Scratch as a Formative Feedback Tool to Assess Computational Thinking

Abstract: This study investigated if using Dr. Scratch as a formative feedback tool would accelerate students' Computational Thinking (CT). Forty-one 4th-6th grade students participated in a 1-hour/week Scratch workshop for nine weeks. We measured pre- and posttest results of the computational thinking test (CTt) between control (n = 18) and treatment groups (n = 23) using three methods: propensity score matching (treatment = .575; control = .607; p = .696), information maximum likelihood technique (treatment effect = -… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…In addition to identifying these traits, Dr. Scratch then extrapolates and assigns a CT score to projects, thus providing feedback to both educators and learners about the CT skills present in their work (Moreno-León et al, 2015, Moreno-León et al, 2017. What makes Dr. Scratch a powerful tool, however, is the general consensus on its effectiveness (Browning, 2017;Lawanto, 2016;Oluk & Korkmaz, 2016).…”
Section: Using Dr Scratchmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition to identifying these traits, Dr. Scratch then extrapolates and assigns a CT score to projects, thus providing feedback to both educators and learners about the CT skills present in their work (Moreno-León et al, 2015, Moreno-León et al, 2017. What makes Dr. Scratch a powerful tool, however, is the general consensus on its effectiveness (Browning, 2017;Lawanto, 2016;Oluk & Korkmaz, 2016).…”
Section: Using Dr Scratchmentioning
confidence: 99%
“…Lawanto (2016), for example, concluded that Dr. Scratch was well suited to assess computational skills, which in turn helped teachers understand students' strengths and weaknesses in programming. Browning (2017) conducted a pre/posttest study in which two groups of 5th-6th graders had a treatment group assessed by Dr. Scratch for the presence of CT skills, and where the control group was assessed by other CT tests. They found that the development in students' programming skills in Scratch would relate to similar increases in their computational thinking skills or improvements in their computational thinking levels.…”
Section: Using Dr Scratchmentioning
confidence: 99%
See 2 more Smart Citations
“…It encompasses the mental skills and practices needed to design computations that can let computers perform tasks for us, and to explain and interpret the world as a complex system of information processes (Denning & Tedre, 2019;Lai, 2021). The provision of opportunities to further stimulate the development of CT, and to enable pupils to acquire the associated skills, entails demands on both the environment and the task (Kong & Abelson, 2019;Rich & Browning, 2022;Yadav et al, 2016).…”
Section: Introductionmentioning
confidence: 99%